2011
DOI: 10.1038/ijo.2011.61
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported and measured anthropometric data and risk of colorectal cancer in the EPIC–Norfolk study

Abstract: Background: Epidemiological studies have shown inconsistent results for the association between body size and colorectal cancer (CRC) risk. Inconsistencies may be because of the reliance on self-reported measures of body size. Objective: We examined the association of self-reported and directly assessed anthropometric data (body height, weight, body mass index (BMI), waist, hip, waist-to-hip ratio (WHR) and chest circumference) with CRC risk in the EPIC-Norfolk study. Design: A total of 20 608 participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 55 publications
0
31
1
1
Order By: Relevance
“…Some previous studies reported that WHR might be an independent risk factor for cancer, but most of these studies used a case-control design, anthropometric measures were not taken directly but were self-reported or did not adjust for BMI in their analyses. (16-18) We found that all observed WHR-cancer associations disappeared after adjusting for BMI, which suggests that general obesity, probably through excessive endogenous sex hormone production in adipose tissue, might play a more important role in the etiology of cancer than central adiposity, which is more closely related to insulin resistance than general obesity. (4) We found similar cancer risk associations for waist circumference and BMI, which strengthen the hypothesis that waist circumference, similar to BMI, is more strongly correlated with total body fat than visceral fat, especially among elderly individuals.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some previous studies reported that WHR might be an independent risk factor for cancer, but most of these studies used a case-control design, anthropometric measures were not taken directly but were self-reported or did not adjust for BMI in their analyses. (16-18) We found that all observed WHR-cancer associations disappeared after adjusting for BMI, which suggests that general obesity, probably through excessive endogenous sex hormone production in adipose tissue, might play a more important role in the etiology of cancer than central adiposity, which is more closely related to insulin resistance than general obesity. (4) We found similar cancer risk associations for waist circumference and BMI, which strengthen the hypothesis that waist circumference, similar to BMI, is more strongly correlated with total body fat than visceral fat, especially among elderly individuals.…”
Section: Discussionmentioning
confidence: 84%
“…(15) However, previous reports of central obesity and cancer risks have not been consistent,(16-18) and the literature lacks studies from Asian populations. Additionally, it has been shown that there are population differences in body fat distribution in comparisons between Asians and other ethnic and racial groups.…”
mentioning
confidence: 99%
“…Increased central adiposity (as measured by waist circumference and/or waist-hip-ratio) has been associated with increased risk of colorectal cancer in most cohort studies and meta-analyses (Larsson & Wolk, 2007; Moghaddam et al , 2007; Ning et al , 2010; Oxentenko et al , 2010; Park et al , 2011; Schoen et al , 1999; Wang et al , 2008). Findings regarding dyslipidemia, including total cholesterol (Jarvinen et al , 2001; Schatzkin et al , 1988; Tornberg et al , 1986) and triglycerides (Tsushima et al , 2005; van Duijnhoven et al , 2011) have been inconsistent or null.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported height and weight have repeatedly been shown to be valid for identifying relationships in epidemiologic studies, as self-reported and measured weights show strong correlation. [2526] Previous studies have also demonstrated that recalled weight at 18 years of age and self-reported height are highly valid,[27] including Troy et al (1995) in which women aged 25–42 in the Nurses’ Health Study II were examined. [28]…”
Section: Methodsmentioning
confidence: 99%